Antimicrobial activity of illudalane and alliacane sesquiterpenes from the mushroom Gloeostereum incarnatum BCC41461. (June 2017) - Bunbamrung, Nantiya; Intaraudom, Chakapong; Dramae, Aibrohim; Boonyuen, Nattawut; Veeranondha, Sukitaya; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Graphical abstract: Highlights: Eleven new illudalane sesquiterpenes were isolated from the mushroom Gloeostereum incarnatum BCC41461. Isolated compounds were evaluated for antimicrobial activity and for cytotoxicity against both cancerous and non-cancerous cells. Illudalane sesquiterpenes exhibited a broad spectrum of antimicrobial activity. Abstract: Eleven previously undescribed sesquiterpenes1 –4 (named incarnatins A − D) and6 –12 (named incarnolactones A − C, incarnatin E, incarnate methyl ester, incarnetic acid, and incarnatenin), together with two known compounds, chondrosterin B (13 ) and ( E )-dictyochromenol (14 ), were isolated from the mushroom Gloeostereum incarnatum BCC41461. The chemical structures were determined on the basis of 1D and 2D NMR spectroscopic information together with their specific rotation values for identification of the stereochemistry. Compounds were evaluated for antimicrobial activity, including antimalarial, antituberculosis, and anti- Bacillus cereus, along with cytotoxicity against both cancerous and non-cancerous cells. Compounds1 and8 exhibited antimalarial (IC50 9.80 μg/mL) and anti- B. cereus (MIC 25 μg/mL) activities, respectively, with low cytotoxicity. In addition, incarnatin B (2 ) and chondrostenin B (13 ) displayed strong antimalarial activity with respective IC50 values of 3.93 and 3.10 μg/mL, while compound14 showed anti-TB and anti- B. cereus with MIC 12.50 and 1.56 μg/mL, respectively.